Emotions, Triggers, and Traits: A Thematic Analysis of Neuromarketing in Digital Buying - Shahzad, Khurram; Khan, Shahzaib; Raza, Farhan; Kamal, Muhammad Hassan; Ullah, Sami (Pakistan Journal of Humanities and Social Sciences, 2025)
The research delves into the convergence of neuromarketing, emotional triggers, and personality traits to inform consumer purchasing behavior in digital environments. Filling an important gap in the literature, it constructs a robust thematic framework that combines neuroscience measures, psychological theory, and marketing approach to decipher implicit purchasing behavior. The research was prompted by the growing prevalence of using emotional cues in digital marketing and the ethical oxymoronic nature of biometric consumer targeting. Through a thematic analysis, the study combined 400 peer-reviewed papers (2020–2025) from Scopus and Web of Science. It grouped findings into five themes: neuromarketing tools, emotional triggers, personality traits, strategic uses, and ethical issues. Major findings are that methods such as fMRI, EEG, and eye-tracking reveal neural responses in real time, whereas personality traits like neuroticism and impulsiveness enhance the strength of affective stimuli like FOMO and urgency. Theories like AIDA, ELM, TPB, and Prospect Theory explained these behaviors. This work adds value by providing an integrated conceptual model of neuroscientifically based digital purchasing behavior. It emphasizes the double-edged sword of neuromarketing: greater campaign impact and increased ethical issues. Subsequent research must prioritize cultural diversity, integration of real-time data, and ethical governance models for ensuring proper application.